Microscopic and Genetic Characterization of Bacterial Symbionts With Bioluminescent Potential in Pyrosoma atlanticum - Berger, Alexis; Blackwelder, Patricia; Frank, Tamara; Sutton, Tracey T.; Pruzinsky, Nina M.; Slayden, Natalie; Lopez, Jose V. (Frontiers in Marine Science, 2021)
The pelagic tunicate pyrosome, Pyrosoma atlanticum, is known for its brilliant bioluminescence, but the mechanism causing this bioluminescence has not been fully characterized. This study identifies the bacterial bioluminescent symbionts of P. atlanticum collected in the northern Gulf of Mexico using several methods such as light and electron microscopy, as well as molecular genetics. The bacteria are localized within the pyrosome light organs. Greater than 50% of the bacterial taxa present in the tunicate samples were the bioluminescent symbiotic bacteria Vibrionaceae as determined by utilizing current molecular genetics methodologies. A total of 396K MiSeq16S rRNA reads provided total pyrosome microbiome profiles to determine bacterial symbiont taxonomy. After comparing with the Silva rRNA database, a Photobacterium sp. r33-like bacterium (which we refer to as “Photobacterium Pa-1”) matched at 99% sequence identity as the most abundant bacteria within Pyrosoma atlanticum samples. Specifically designed 16S rRNA V4 probes for fluorescence in situ hybridization (FISH) verified the Photobacterium Pa-1 location as internally concentrated along the periphery of each dual pyrosome luminous organ. While searching for bacterial lux genes in two tunicate samples, we also serendipitously generated a draft tunicate mitochondrial genome that can be used for Pyrosoma atlanticum identification. Scanning (SEM) and transmission (TEM) electron microscopy confirmed the presence of intracellular rod-like bacteria in the light organs. This intracellular localization of bacteria may represent bacteriocyte formation reminiscent of other invertebrates.